2021
DOI: 10.3390/polym13183159
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Reinforced Poly(ε-caprolactone)/Epoxy Blends for Superior Mechanical and Self-Sensing Performance in Multiscale Glass Fiber Composites

Abstract: In this paper, a novel carbon nanotube (CNT) polycaprolactone (PCL), epoxy, and glass fiber (GF) composite is reported. Here, the nanoreinforced composites show a flexural strength increase of around 30%, whereas the interlaminar shear strength increases by 10–15% in comparison to unenhanced samples. This occurs because the addition of the CNTs induces a better PCL/epoxy/GF interaction. Furthermore, the nanoparticles also give novel functionalities to the multiscale composite, such as strain and damage monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…These results are perfectly consistent with the nanostructure discussed in the previous section. In the literature, however, the opposite effect has also been observed when PCL was added: the increase it caused in viscosity led to better-dispersed CNTs and, consequently, better electrical properties [ 39 , 40 ]. This is probably because the experimental procedure used for preparing the NCs was different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are perfectly consistent with the nanostructure discussed in the previous section. In the literature, however, the opposite effect has also been observed when PCL was added: the increase it caused in viscosity led to better-dispersed CNTs and, consequently, better electrical properties [ 39 , 40 ]. This is probably because the experimental procedure used for preparing the NCs was different.…”
Section: Resultsmentioning
confidence: 99%
“…In ternary epoxy/PCL/CNT nanocomposites, the PCL increases the viscosity of the blend which, in turn, improves the dispersion of the CNTs [ 39 , 40 ] so that a smaller amount is necessary for the nanocomposites to become semiconductive.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of hydrophobic materials such as ethyl cellulose, polycaprolactone (PCL), poly (lactic-co-glycolic acid), and polylactic acid in sustaining drug release ( Sánchez-Romate et al, 2020 ; Ahmadi et al, 2022 ; Wang S. et al, 2022 ; Dodda et al, 2022 ; Lee et al, 2022 ; Vlachopoulos et al, 2022 ). PCL, a hydrophobic material processing good biocompatibility, is extensively involved in the preparation of biomedical materials ( Jiménez-Suárez et al, 2020 ; Bazzolo et al, 2021 ; Sánchez-Romate et al, 2021 ; Baghali et al, 2022 ; Setia Budi et al, 2022 ; Shahverdi et al, 2022 ). In the treatment of osteoporosis, simvastatin (SIM) has been exploited for inducing bone regeneration ( Castro et al, 2018 ; Rezk et al, 2020 ; Karanikola et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this latter area, PCL is a good candidate as a thermoplastic phase [ 18 ] in epoxy systems as it both improves the fracture toughness of the original matrix and promotes the self-healing abilities of the resulting blend [ 12 , 19 ]. In fact, the addition of PCL and other thermoplastic phases has proved to have excellent capabilities to enhance interlaminar and impact properties in fiber-reinforced composites, although a reduction in the glass transition temperature can be also observed [ 20 , 21 ]. Other approaches such as supramolecular thermosets can avoid this effect of Tg decrease as they do not incorporate a second phase; nevertheless, they are usually activated by other external stimuli rather than temperature, such as pH [ 15 ].…”
Section: Introductionmentioning
confidence: 99%